2018
DOI: 10.1002/esp.4363
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the roles of asymmetric uplift, normal faulting and groundwater flow to drainage rearrangement in an emerging karstic landscape

Abstract: Landscape adjustment to tectonic, lithologic and climatic forcing leads to drainage reorganization and migration of divides. The respective contribution of these forcings, especially on carbonate landscapes is not well defined. Here, we have addressed this issue by combining field observations, satellite image interpretation and digital elevation model (DEM) quantitative analysis to assess drainage response to spatially heterogeneous rainfall, asymmetric uplift, and normal faulting on an emerging carbonated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…This result partly explains the ubiquitous uplifted Pleistocene coral reef sequences that festoon the islands of the Banda arc (Figure 1). Although some are uplifted due to tectonic contraction (for instance, Sumba island, Authemayou et al., 2018, Miller et al., 2021, or SE Sulawesi, Pedoja et al., 2018), the background uplift of the region is induced by the relaxation of the dynamic topography. This motion is well localized around the basin, while the Australian margin conversely continues to subside at present.…”
Section: Resultsmentioning
confidence: 99%
“…This result partly explains the ubiquitous uplifted Pleistocene coral reef sequences that festoon the islands of the Banda arc (Figure 1). Although some are uplifted due to tectonic contraction (for instance, Sumba island, Authemayou et al., 2018, Miller et al., 2021, or SE Sulawesi, Pedoja et al., 2018), the background uplift of the region is induced by the relaxation of the dynamic topography. This motion is well localized around the basin, while the Australian margin conversely continues to subside at present.…”
Section: Resultsmentioning
confidence: 99%
“…In general, river diversion is a less energy‐consuming way of modifying a river network, because it only implies the localized removal of a watershed and does not require significant modification of the network of flow lines (Brocard et al, 2011). However, river diversions have been widely reported, but the exact processes involved in the diversions are generally poorly documented, because the diagnostic features of such processes generally quickly disappear after a diversion, which means that proving diversion is difficult (Bishop, 1995; Brocard et al, 2011; Authemayou et al, 2018). In the case of our study area, the role of river diversion and the occurrence of top‐down process is found to be prominent during the drainage realignment in the Gunawari River basin.…”
Section: Discussionmentioning
confidence: 99%
“…Drainage reorganization involves modification of drainage lines and this may be caused by tectonic activity (Bishop, 1995). An increasing number of studies in river basins around the world reveal show large‐scale landscape changes and drainage reorganization (Almeida‐Filho & Miranda, 2007; de Fátima Rossetti et al, 2005; Franzinelli & Igreja, 2002; Silva et al, 2007), for example, the Amazon River basin (Authemayou et al, 2018; Babault et al, 2012; Hayakawa et al, 2010; Mantelli et al, 2009; Rossetti & Góes, 2008); the Yarlung Zangbo–Brahmaputra River system (Bracciali et al, 2015; Ghosh et al, 2015; Jiang et al, 2016; Korup & Montgomery, 2008; Lahiri & Sinha, 2012; Lang & Huntington, 2014; Schmidt et al, 2015; Zeitler et al, 2001; Zhang et al, 2012) and the Three River watershed (Whipple et al, 2017; Yang et al, 2016). Plate tectonics and the evolution of passive margins have been identified as critical for understanding the long‐term landscape evolution and drainage history (Bishop, 1995, 1998; Harel et al, 2019; Summerfield, 1985, 1991), along with them being the prime cause of macroscale “drainage rearrangement” phenomenon (Bishop, 1986, 1988; Driscoll & Karner, 1994; Oilier, 1982; van de Graaff et al, 1977).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations